2012
DOI: 10.1093/bja/aes279
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block for postoperative analgesia after Caesarean delivery performed under spinal anaesthesia? A systematic review and meta-analysis

Abstract: The transversus abdominis plane (TAP) block is a field block that provides postoperative analgesia for abdominal surgery. Its analgesic utility after Caesarean delivery (CD) remains controversial. This systematic review and meta-analysis examines whether TAP block can reduce i.v. morphine consumption in the first 24 h after CD. The authors retrieved randomized controlled trials comparing TAP block with placebo in CD. Postoperative i.v. morphine consumption during the first 24 h was selected as a primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(99 citation statements)
references
References 44 publications
3
84
1
1
Order By: Relevance
“…In addition, as the cumulative fentanyl consumption was significantly lower in the T R S F and T RF groups at 2 h postoperatively, as compared with that in group T R , the early analgesic-sparing effect associated with perineural fentanyl may have been mediated by systemic effects due to peripheral uptake. The TAP block is commonly used during a cesarean delivery, in which it forms part of a multimodal postoperative analgesic regimen (2)(3)(4)(5). Previous studies have demonstrated that a single injection of TAP block was able to significantly improve post-cesarean analgesia in the absence of spinal morphine; however, the analgesic duration was limited, as compared with intrathecal morphine (2-4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as the cumulative fentanyl consumption was significantly lower in the T R S F and T RF groups at 2 h postoperatively, as compared with that in group T R , the early analgesic-sparing effect associated with perineural fentanyl may have been mediated by systemic effects due to peripheral uptake. The TAP block is commonly used during a cesarean delivery, in which it forms part of a multimodal postoperative analgesic regimen (2)(3)(4)(5). Previous studies have demonstrated that a single injection of TAP block was able to significantly improve post-cesarean analgesia in the absence of spinal morphine; however, the analgesic duration was limited, as compared with intrathecal morphine (2-4).…”
Section: Discussionmentioning
confidence: 99%
“…TAP block can be performed by injecting LAs into the tissue plane between the internal oblique and the transversus abdominis via a blind technique, based on surface anatomy landmarks (1,2) and, most recently, an ultrasound (US)-guided technique under direct vision (3,4). TAP block has been shown to effectively provide analgesia, without the requirement for intrathecal morphine, as part of a multimodal analgesic regimen following cesarean delivery (5). However, the duration of analgesia provided by a single-injection TAP block has been demonstrated to be shorter, as compared with that of the intrathecal morphine (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2010 Cochrane Review of the analgesic effectiveness of TAP block after abdominal surgery included only five trials. 5 In 2012, Abdallah et al subsequently reported a systematic review and meta-analysis of TAP block for pain relief after Cesarean delivery that included results from five trials, 6 and in 2013, Champaneria et al…”
mentioning
confidence: 99%
“…12 Additives to local anaesthetics like opioids, ketamine and α2 agonists like clonidine and dexmeditomidine have been successfully used in peripheral nerve blocks to increase the duration of postoperative analgesia. Various studies have been conducted for the post-operative analgesia in abdominal surgeries by comparing the transverses abdominis plane (TAP) block with placebo or local wound infilitration.…”
Section: Introductionmentioning
confidence: 99%